Pengaruh Desain Produk, Kualitas Produk dan Viral Marketing Terhadap Keputusan Pembelian Produk Erigo - Fauzi, Abdullah Muhaimin Nur; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The impact of Product Design, Product Quality, and viral marketing on consumer purchasing decisions was investigated in this research. The study's population comprised students from the 2020 cohort at FEB UNISMA, Malang City, from whom a sample of 85 individuals was drawn using particular sampling procedures. Data analysis was conducted with the SPSS application. Multiple linear regression analysis was the statistical technique employed. This study aims to deepen understanding regarding the factors influencing consumer choices when acquiring Erigo products. The results demonstrate that Product Design, Product Quality, and Viral Marketing significantly influence consumer decisions to purchase Erigo products. Keywords: Produck Design, Produck Quality, and Viral Marketing